North American natural gas model impact of cross-border trade with Mexico - Felipe Feijoo; Daniel Huppmann; Larissa Sakiyama; Sauleh Siddiqui (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Natural gas as a source of energy has attracted a lot of interest as its emissions rate and price are lower than other fossil fuel energy sources. In the U.S., natural gas-fired power generation has been rising, as coal has declined as a share of the fuel mix. Likewise, Mexico recently launched its energy reform with focus on greatly expanding use of natural gas over other fossil fuels, primarily in the energy sector, by opening the market to private investors. These recent economic and policy changes, along with increasing gas production in the U.S. (shale gas boom) are likely to drive the natural gas market in North America in a new direction. For instance, the Annual Energy Outlook 2015 describes the U.S. for the first time as a net exporter of natural gas (via pipelines and LNG) by 2017. In order to study the current North American gas market with its new regulations like the Mexican energy reform, this paper presents the North American Natural Gas Market Model(NANGAM). We propose a long-term partial-equilibrium model of the United States, Mexican, and Canadian gas markets. NANGAM considers more granular details regarding market regions and pipelines in Mexico than other existing models, allows for endogenous infrastructure expansion, and is built in five year time-steps up to 2040, considering three seasons (low, high, and peak demand) for each time-step. NANGAM is calibrated using up-to-date data, which reflects current gas market trends, such as the increasing U.S. shale gas production. Using NANGAM, we assess the implications of the Mexican energy reform using a set of ad-hoc future scenarios. Results from the model show that, in the case of disappointing development of natural gas production in Mexico, the census region US7 (Texas and adjacent states) is the most affected, reaching an increase of natural gas production of up to 12% by 2040 compared to baseline projections.
Keywords: Q41; L71; Q37; C61; 330; North American natural gas scenarios; Mexican energy reform; dynamic market equilibrium model; mixed complementarity problem; infrastructure investment; capacity investment